The Excellence of Moulana Ahmad Raza Khan in Hadith Science: An Analytical Discourse - Tayyab, Zubair; Rao, Muhammad Atif Aslam (Al-Irfan, 2021)
The scholars of the subcontinent have distinctly rendered unmatched services in Hadith of the Holy Prophet صلى الله عليه وسلم .One of these enlightened scholars is Moulana Ahmad Raza Khan of Bareli, India. Besides, deep involvement in Islamic jurisprudence, he had exceptional insight into Ahadith. He was an authority in principles of Hadith, types of Hadith, narrators of the Hadith, the causes of the Hadith and details of Asma’ al-Rijal. His books are evidence of his profound vision and deeper knowledge of all sciences of Hadith. That’s why various contemporaries rightly addressed him as the Amir alMu’minin of Hadith. ( ) This article includes insight of Moulana Ahmad Raza Khan in the science of Hadith. Moreover, the research presented here outlines the distinction of Moulana in various aspects of Hadith science. Finally, with significant references and arguments, the researcher concludes that the glory and perfection of Moulana Ahmad Raza Khan should be openly acknowledged in Hadith and related sciences like other sciences, and his valuable scientific capital should be utilized. The suggestions presented at the end is worth it for all students of Hadith Science.